Conductivity studies of Li2O-TiO2-P2O5 system - Majid, Siti Rohana; Subban, R.H.Y.; Faizal, A.F.A. (2009)
The system Li2O-TiO2-P2O5 is prepared in order to investigate the effect of heat and mechanical treatment on the conductivity. Mechanical milling ( MM) method was used to prepare the system. The effects of sintering temperature and mechanical milling treatment on the system Li2O-TiO2-P2O5 have been investigated using electrochemical impedance spectroscopy, X-ray differential analysis and laser particle sizer. Some crystalline phases with slight amorphous nature were detected in the highest conducting sample. The samples were sintered at several temperatures from 300 to 1000 degrees C. The sample treated at 800 degrees C obtained the smallest particle size of about 300 nm. The sample treated at 800 degrees C and milled for 4 h obtained the highest conductivity with a value of 8.89 x 10(-5) S cm(-1). The activation energy was found to be as low as 0.075 eV.